Perbandingan Kedalaman Berbeda Terhadap Pertumbuhan Rumput Laut (Euchema cottonii) Pada Metode Modifikasi Keramba Jaring Apung di Teluk Jepara - Astiyani, Wahyu Puji; Oktavian, Ganis; Febriani P., Vini Taru; Kristiana, Indra; Akbarurrasyid, Muhammad; Prama, Ega Aditya (Jurnal Perikanan Unram, 2025)
Seaweed farming is one of the most important aquaculture sectors in Indonesia, contributing significantly to the national economy. Among various species, Eucheuma cottonii is widely cultivated due to its high carrageenan content and industrial value. Optimizing environmental conditions, such as culturing depth, is crucial to improving growth performance and productivity. This study evaluated the effect of different culturing depths on the growth of E. cottonii using a modified floating net cage system in Jepara Bay. The experiment applied three depth treatments—25 cm (A), 45 cm (B), and 65 cm (C)—each with two replications. Seaweed growth was monitored over 49 days and assessed based on absolute weight and specific growth rate (SGR). Results showed that seaweed cultivated at 25 cm had the highest growth performance, with an absolute weight of 102.2 g and the highest SGR, whereas the lowest values were recorded at 65 cm. ANOVA analysis confirmed a significant effect of depth on growth (p < 0.05), supported by Duncan’s test indicating clear differences among treatments. Water quality parameters (temperature, salinity, pH, and dissolved oxygen) remained within optimal ranges, suggesting depth was the primary factor influencing growth. The findings highlight that shallower depths promote greater light penetration and photosynthetic efficiency, thus enhancing E. cottonii growth. A culturing depth of 25 cm is recommended for optimal productivity in similar cultivation systems.